PENGARUH MONITORING HIPERTENSI BERBASIS APLIKASI TERHADAP KEPATUHAN MELAKUKAN TERAPI JUS PADA PASIEN HIPERTENSI - Faridah, Ida; Afiyanti, Yati; Huriyanah, Huriyanah (Nusantara Hasana Journal, 2022)
Hypertension is one of the non-communicable diseases and this requires very serious attention and needs to be taken nationally, where the prevalence is high and many individuals do not realize that they have hypertension, they know that they are suffering when they do a health check at the hospital. health services, because they feel pain or other complaints, hypertension is often called "the silent killer". The purpose of this study was to determine the effect of using applications for nurses and people with hypertension to monitor and control therapy compliance. This study is a quantitative study using a Quasi-experimental design with a One Group Pretest Posttest design. In this study, before and before the intervention was made, firstly assessing adherence to therapy in hypertensive patients (pre-test-posttest). This study was conducted from March to September 2021 with 98 patients as respondents who suffered from Hypertension in Tangerang Regency. It was concluded that there was a significant difference before and before the implementation of adherence, the results of P value 0.05 which means the alternative hypothesis (Ha) is accepted in other words there is an effect of the use of monitoring applications on adherence to therapy in hypertensive patients in the district. Tangerang.